Did Dionysius of Fourna Follow the Material Recipes Described in His Own Treatise? A First Analytical Investigation of Four of His Panel Paintings - Thomas Mafredas; Eleni Kouloumpi; Stamatis C. Boyatzis (Heritage, 2021)
A research protocol based on imaging techniques and physicochemical analyses was designed and carried out in order to investigate the construction technology of four panel paintings produced by a very important 18th century artist, hieromonk Dionysius from Fourna. Dionysius was the first painter of the post-Byzantine period who wrote an artists’ manual for the Eastern Orthodox painting art: he recorded and described in his treatise ‘Hermeneia of Art Painting’ the materials and construction techniques of the 18th century Christian painting. The contribution of Dionysius and his ‘Hermeneia of the Painting Art’ is decisive because it gathers all the previously scattered advice and guidelines about the construction of panel paintings and the information quoted by him is probably the only official recorded source of Eastern Orthodox art technology. In this context, four panel paintings signed by Dionysius were selected for scientific research: it is the first time that an effort is made to analytically characterize the materials used by the hieromonk, to recognize the construction technology, and examine whether it follows the recipes included in his manuscript or not.